Evaluating Consumers’ Adoption of Renewable Energy - Khalid, Bilal; Urbański, Mariusz; Kowalska-Sudyka, Monika; Wysłocka, Elżbieta; Piontek, Barbara (Energies (Basel), 2021)
The purpose of this study was to evaluate the consumers’ adoption of renewable energy in Poland. The study focused on finding out the factors that influence the adoption of the technology, considering its importance in conserving the environment. The study was conducted using a quantitative method, with primary data collected from 467 households using renewable energy technology in Poland. The research adopted the TAM model. The independent variables of the study included renewable energy initial cost, environmental concern, risk and trust for renewable energy, ease of use, financial incentives, and relative advantage. The dependent variable was renewable energy adoption. Structural equation modelling (SEM) was used to analyze the study hypotheses. The research found out that environmental concerns, ease of use, financial incentives, and relative advantage have a positive and significant influence on adoption of renewable energy technology in Poland. However, renewable energy initial cost and risk, and trust for renewable energy did not significantly influence renewable energy adoption. The study recommended that the stakeholders should consider the aspects of environmental concern as a key role player in pushing for adoption of renewable energy. The government, non-governmental organizations, and concerned stakeholders should consider giving incentives towards renewable energy adoption. Creating awareness regarding the benefits and strengths of renewable energy should be prioritized to the households.